Evaluation of the effect of local Bovine Amniotic Fluid on Osseointegration of Titanium Implants: A Histologic and Histomorphometric Study - Istek, Ozmen; Tanrisever, Murat; Aydin, Melek Atille; Pak, Pinar; Eroksuz, Hatice; Karabulut, Burak; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
The aim of this study was to histologically and histomorphometrically investigate the effect of locally applied bovine amniotic fluid (BAF) on osseointegration levels in implants. Adult female Sprague-Dawley rats weighing 300-350 g were used as subjects. The rats were divided into two groups: the sham-operated control group (n=10) and the local BAF group (n=10). Implant cavities were created in the tibias of all subjects under sterile saline cooling with rotating instruments. Local BAF was applied to all implant sockets before the implants were placed. Rats were sacrificed after a four-week osseointegration period. Histological staining was performed using hematoxylin and eosin staining to analyze the osseointegration. Examinations of the bone implant connection (BIC) and peri-implant bone formation (PBF) were performed using a light microscope and an image analyzer. As a result of the analysis, the mean BIC value was 40.3 +/- 4.9 for the sham-operated control group and 45.2 +/- 7.7 for the local BAF group. The mean PBF was 39.9 +/- 6.3 for the sham control group and 40.5 +/- 5.7 for the local BAF group. A statistically significant difference was found between the sham control group and the local BAF group for the BIC and PBF values (P>0.05; P >0.05; P : 0.11; P : 0.83). The application of local BAF to the implant socket did not have a clear positive effect on implant osseointegration. More studies are needed to clarify the association between local BAF and osseointegration.
Evaluación del efecto del líquido amniótico bovino local sobre la osteointegración de implantes de titanio: un estudio histológico e histomorfométrico
Keywords: Bovine amniotic fluid; titanium implant; osseointegration; bone implant connection; bone implant contact